Secondary glaucoma in uveitis: comparison of the optic nerve head morphology among a nonmydriatic fundus camera, HRT, and SD-OCT. Issue 3 (May 2018) - Pahlitzsch, Milena; Klamann, Matthias K.J.; Jacob, Saskia; Erb, Carl; Winterhalter, Sibylle; Torun, Necip; Maier, Anna-Karina B.; Bertelmann, Eckart
Purpose: To assess the correlation between the disc damage likelihood scale (DDLS) objectively measured by a nonmydriatic fundus camera, confocal laser scanning ophthalmoscopy (HRT3), and spectral-domain optical coherence tomography (SD-OCT) in uveitic glaucoma. Methods: A total of 59 patients with uveitic glaucoma (21 female, 38 male; mean age 56.8 ± 18.7 years) were included in this prospective cross-sectional study. All patients were measured by the Kowa Nonmyd WX 3D camera (2D/3D nonmydriatic retinal camera, Kowa Company), the HRT3 (Heidelberg Engineering), and SD-OCT (Carl Zeiss Meditec) by one examiner on the same day. All 3 devices graded the optic disc topography. Statistical data were calculated using SPSS (v 20.0, SPSS). Results: In patients showing borderline results in one of the modalities (n = 45), the DDLS showed a significant correlation with the retinal nerve fiber layer (p = 0.016), while Moorfields regression analysis (p = 0.550) and glaucoma probability score (p = 0.629) did not correlate significantly. The highest predictive power was demonstrated by the objectively measured DDLS (area under the receiver operating characteristic curve 0.445-0.588), compared to R. Burk (0.149-0.375) and F.S. Mikelberg (0.033-0.450) coefficients considering HRT and optical coherence tomography. Conclusions: In this study cohort, the objective DDLS showed the highest predictive power and thus is a reliable tool in diagnosing uveitic glaucoma. These 3 devices cannot be used interchangeably. As diagnosis and follow-ups are challenging in uveitis patients, the stereophotography is additionally a valuable tool.